Coating agent
A coating agent with fine metal particles, inorganic polymers, and nanofibers addresses adhesion and refractive index issues, providing durable, hydrophilic films with enhanced resistance and transparency.
Patent Information
- Application Number
- JP2024193750
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-04
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing superhydrophilic coating films face issues with adhesion to substrates, especially when thick, and are prone to interference fringes due to refractive index differences, with organic polymers compromising transparency, hardness, and durability, and inorganic coatings requiring UV irradiation or high-temperature processing.
A coating agent comprising fine particles of a water-insoluble metal compound, an inorganic polymer, and transparent nanofibers dispersed in a solvent, with superhydrophilic functional groups and refractive index modifiers, forming a coating film that enhances adhesion, durability, and suppresses interference fringes.
The coating agent achieves excellent hydrophilicity, hardness, and durability, maintaining hydrophilicity over time, with improved adhesion and resistance to temperature, humidity, and weathering, while minimizing interference fringes.
Smart Images

Figure 2025010414000001 
Figure 2025010414000002 
Figure 2025010414000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating agent capable of forming a coating film exhibiting superhydrophilicity. [Background technology]
[0002] Conventionally, development of superhydrophilic coating materials has been promoted for the purpose of improving anti-fogging and anti-soiling properties. As materials that exhibit hydrophilicity, for example, organic materials using organic polymers containing hydroxyl groups (e.g., Patent Document 1), inorganic materials using photocatalysts (e.g., Patent Document 2), inorganic silica materials using silica (e.g., Patent Documents 3 and 4), etc. are known. However, with organic materials, it is necessary to form a coating by UV curing or heat curing, and on-site application may be difficult. In addition, in order for a hydrophilic film made of titanium oxide to exhibit hydrophilicity, it is necessary to irradiate it with ultraviolet rays. Therefore, when it is used in an environment where ultraviolet rays are not sufficiently irradiated, such as indoors, there is a problem that hydrophilicity cannot be exhibited.
[0003] As a film that can exhibit hydrophilicity regardless of whether or not it is in an environment where ultraviolet rays are sufficiently irradiated, for example, a superhydrophilic film made of amorphous silica produced by a sol-gel method has been proposed (see, for example, Patent Document 5). In addition, a superhydrophilic film has also been proposed using amorphous silica to which a hydrophilic functional group has been introduced (see, for example, Patent Documents 6 and 7). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-356201 A [Patent Document 2] Patent No. 3844182 specification [Patent Document 3] Japanese Patent Application Publication No. 9-156959 [Patent Document 4] JP 2015-096459 A [Patent Document 5] JP 2008-174617 A [Patent Document 6] Republished Publication No. 2013-001975 [Patent Document 7] JP 2000-239607 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the coating film made of inorganic polymers such as those produced by the sol-gel method does not have sufficient adhesion to the substrate, and in particular, when the film is made thick, the adhesion to the substrate may decrease. The obtained film has a problem that it has low thermo-hygroscopic resistance (an environment in which temperature and humidity are constantly applied) and is prone to interference fringes due to the difference in refractive index between the substrate and the coating film. In such a case, it is possible to add an organic polymer to impart flexibility to the coating film, but this may cause problems such as reduced transparency, hardness, and durability of the obtained coating film. In addition, the present inventors have found that the inorganic hydrophilic coating liquid containing an amorphous silicate compound obtained by hydrolysis and condensation of a tetrafunctional silicon compound proposed in Patent Document 6 has room for improvement in moist heat resistance and abrasion resistance through their studies. The siliceous coating film proposed in Patent Document 7 is one that imparts hydrophilicity by converting sulfide groups to sulfonic acid groups, and requires heating at about 200°C to form the coating.
[0006] In addition, coating agents made of inorganic polymers can complicate the painting process, and depending on the substrate, such as substrates with low hydrophilicity, the coating agent can have poor leveling properties and insufficient workability.
[0007] The present invention has been made to solve such problems. One of the objects of the present invention is to provide a coating agent capable of obtaining a coating film excellent in hardness and durability, adhesion to a substrate, anti-fogging property, anti-fouling property, and workability. An object of the present invention is to provide a coating agent which is excellent in hydrophilicity, warm water resistance and coatability and is capable of forming a coating film which is less susceptible to cracking. Another object of the present invention is to provide a coating agent capable of forming a coating film which is excellent in temperature and humidity resistance, heat resistance and weather resistance and which can maintain hydrophilicity for a long period of time. Furthermore, another object of the present invention is to provide a coating agent capable of forming a coating film having excellent hydrophilicity and capable of suppressing interference fringes caused by the difference in refractive index between the substrate and the coating film. [Means for solving the problem]
[0008] The object of the present invention is achieved by the following [1] to
[19] . [1] A coating agent in which fine particles of a water-insoluble metal compound, an inorganic polymer, and transparent nanofibers are dispersed in a solvent; [2] The coating agent according to [1] above, wherein the transparent nanofiber is a nanofiber made of a polysaccharide; [3] The coating agent according to [2] above, wherein the polysaccharide nanofiber is a cellulose nanofiber or a nanofiber having a structural unit of chitin or chitosan; [4] Any of the coating agents according to [1] to [3] above, wherein the content of the transparent nanofibers is 0.1 to 10 mass% based on the total solid content; [5] The coating agent according to any one of [1] to [4] above, wherein the metal fine particles have a particle diameter of 1 to 100 nm, and the transparent nanofibers have a fiber diameter of 2 to 100 nm; [6] A coating agent in which fine particles of a water-insoluble metal compound and an inorganic polymer are dispersed in a solvent, the metal compound having a superhydrophilic functional group; [7] The superhydrophilic functional group has the formula (1): [ka] (In formula (1), R 1 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms, A 1is a monovalent cation.) A sulfonic acid group or a sulfonate group having a structure represented by formula (2): [ka] (In formula (2), R 2 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms, A 2 is a monovalent cation.) the coating agent according to the above [6], wherein the functional group is a carboxylate group, a polyether group, or a ureido group having a structure represented by the following formula: [8] A coating agent in which fine particles of a water-insoluble metal compound, an inorganic polymer, and a refractive index adjuster are dispersed in a solvent; [9] Any of the coating agents according to the above [1] to [8], wherein the metal compound is silicon dioxide.
[10] The coating agent according to [9] above, wherein the refractive index control agent is fine particles of an oxide of at least one metal selected from the group consisting of Mg, Al, Ca, Ti, Zn, Nb, Zr, Sn, Ta, Ce, and Hf;
[11] The coating agent according to any one of the above [1] to
[10] , wherein the inorganic polymer has a structure obtained by condensing silicon alkoxide;
[12] The coating agent according to any one of [1] to
[11] above, wherein the coating agent has a solid content concentration of 0.1 to 30 mass%;
[13] Any of the coating agents according to the above [1] to
[12] , wherein a mass ratio of metal fine particles to inorganic polymer is 20 / 80 to 90 / 10;
[14] An article having a coating film formed by applying the coating agent according to any one of [1] to
[13] above;
[15] A method for applying the coating agent according to any one of the above items [1] to
[14] , comprising a first cleaning step of cleaning a surface to be coated with a cleaning liquid, and a coating step of applying the coating agent while the cleaning liquid remains on the surface to be coated;
[16] The coating method according to
[15] above, further comprising a second cleaning step of cleaning the coated surface with a cleaning liquid before all of the applied coating agent dries;
[17] The coating method according to
[15] or
[16] above, wherein the surface to be coated is a metal oxide or a silicate compound;
[18] The coating method according to
[17] above, wherein the surface to be coated is glass and the first cleaning step is performed using an abrasive for glass;
[19] The coating method according to
[17] above, wherein the surface to be coated is made of ceramics. Effect of the Invention
[0009] According to an embodiment of the present invention, a coating agent capable of forming a coating film having excellent transparency and hardness, adhesion to a substrate, antifogging properties, antifouling properties, and workability can be provided. Furthermore, according to the embodiment of the present invention, it is possible to provide a coating agent capable of forming a coating film that is excellent in hydrophilicity, warm water resistance, and coatability, and is also resistant to cracking. Furthermore, according to the embodiment of the present invention, it is possible to provide a coating agent capable of forming a coating film that is excellent in temperature and humidity resistance, heat resistance, and weather resistance, and that can maintain hydrophilicity for a long period of time. Furthermore, according to the embodiment of the present invention, it is possible to provide a coating agent capable of forming a coating film having excellent hydrophilicity and capable of suppressing interference fringes that occur due to the refractive index difference between the substrate and the coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The components of the coating agent of the present invention, the production method, the method for forming the coating film, etc. will be described below. The coating agent of the present invention is a dispersion of fine particles of a water-insoluble metal compound and an inorganic polymer in a solvent.
[0011] (Water-insoluble metal compound particles) In the present invention, fine particles of a water-insoluble metal compound (hereinafter, sometimes referred to as metal fine particles) are used. As the metal fine particles, fine particles of a metal oxide or metal hydroxide that are insoluble in water can be used. The metal is not particularly limited as long as it is a fine particle that shows water insolubility, and examples thereof include metals represented by the element symbols Mg, Al, Si, Ca, Ti, Zn, Nb, Zr, Sn, Ta, Ce, and Hf. In addition to the oxides or hydroxides of these metals, fine particles containing silicate compounds can also be used. Among these, fine particles containing Si atoms, such as silicon dioxide and silicate compounds, are preferred in terms of excellent hydrophilicity of the resulting coating film.
[0012] Colloidal metal particles are used. The average particle size of the metal particles is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. The average particle size of the metal particles is preferably 100 nm or less. By using metal particles having such a particle size, the transparency and hardness of the resulting coating film can be improved. An example of the colloidal metal particles is colloidal silica. The average particle size of colloidal silica can be measured by the BET method or the like.
[0013] The content (solid content) of metal fine particles in the coating agent is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass, based on the total content (solid content) of metal fine particles and inorganic polymer. If the content of metal fine particles is less than 20% by mass, the hardness of the resulting coating film may decrease. In addition, the content of metal fine particles in the coating agent is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less, based on the total content of metal fine particles and inorganic polymer. If the content of metal fine particles exceeds 90% by mass, the adhesion of the resulting coating film to the substrate tends to decrease, and the hydrophilicity tends to decrease.
[0014] In a second embodiment described later, of the metal compound and the inorganic polymer, at least the metal compound has a superhydrophilic functional group.
[0015] (Inorganic Polymers) The coating agent of the present invention contains an inorganic polymer. The inorganic polymer preferably has, for example, a Si-O bond, an Al-O bond, a Ti-O bond, a Zr-O bond, or a Sn-O bond, and also has a hydroxyl group in the molecule.
[0016] In this specification, the term "inorganic polymer" refers to a concept that includes not only so-called polymers but also oligomers, and includes low polymers having a molecular weight of 10,000 or less. The inorganic polymer may be bonded to another inorganic polymer when forming a coating film.
[0017] As the inorganic polymer, an inorganic polymer obtained from a metal alkoxide, that is, a polymer obtained by hydrolysis of an alkoxy group in a metal alkoxide and further dehydration condensation, can be used. Examples of the metal alkoxide include M(OR)4 (M represents a metal atom, and R represents a hydrogen atom or a monovalent hydrocarbon group), M(OR 3 )3R 4 (M is a metal atom, R 3 is a hydrogen atom or a monovalent hydrocarbon group, R 4 represents a monovalent hydrocarbon group. 3 )2R 4 2 (M is a metal atom, R 3 is a hydrogen atom or a monovalent hydrocarbon group, R 4 represents a monovalent hydrocarbon group.) Examples of the monovalent hydrocarbon group include a methyl group, an ethyl group, a propyl group, and a butyl group.
[0018] When the metal atom is Si, that is, specific examples of silicon alkoxides include tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetraisobutoxysilane, tetra-t-butoxysilane or derivatives thereof, methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-propoxysilane, methyltriisopropoxysilane, methyltri-n-butoxysilane, methyltriisobutoxysilane, methyltri-t-butoxysilane or derivatives thereof, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldi-n-propoxysilane, dimethyldiisopropoxysilane, dimethyldi-n-butoxysilane, dimethyldiisobutoxysilane, dimethyldi-t-butoxysilane or derivatives thereof, etc. Among these silicon alkoxides, tetramethoxysilane and tetraethoxysilane are preferred.
[0019] When the metal atom is Al, specific examples of the aluminum alkoxide include tetraethoxyaluminum, tetraisopropoxyaluminum, and derivatives thereof.
[0020] When the metal atom is Ti, specific examples of titanium alkoxides include tetraisopropoxytitanium, tetra-n-butoxytitanium and derivatives thereof.
[0021] When the metal atom is Zr, specific examples of the zirconium alkoxide include tetra-n-butoxyzirconium, tetra-t-butoxyzirconium or derivatives thereof, zirconium oxynitrate, zirconium oxychloride, and the like.
[0022] When the metal atom is Sn, specific examples of the tin alkoxide include tetra-n-butoxytin, tetra-t-butoxytin and derivatives thereof.
[0023] These metal alkoxides are merely examples, and other metal alkoxides or derivatives thereof can be used. These metal alkoxides or derivatives thereof can be used alone or in combination of two or more kinds.
[0024] The content (solid content) of the inorganic polymer in the coating agent is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass, based on the total content (solid content) of the metal fine particles and the inorganic polymer. If the content of the inorganic polymer is less than 10% by mass, the adhesion of the resulting coating film to the substrate tends to decrease, and the hydrophilicity tends to decrease. In addition, the content of the inorganic polymer in the coating agent is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less, based on the total content of the metal fine particles and the inorganic polymer. If the content of the inorganic polymer exceeds 80% by mass, the hardness of the resulting coating film may decrease.
[0025] (solvent) The coating agent of the present invention contains a solvent. As the solvent, water or a water-containing alcohol-based solvent, or a glycol ether can be used. Examples of alcohol-based solvents include lower aliphatic alcohol-based solvents such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, 2-methylbutanol, sec-pentanol, t-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, 2-ethylbutanol, sec-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,4,6-dimethylheptanol, n-decanol, sec-undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl alcohol, sec-heptadecyl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, and diacetone alcohol. Examples of glycol ethers include ethylene glycol monobutyl ether and its derivatives, propylene glycol monoalkyl ether, ethylene glycol monoalkyl ether, diethylene glycol monobutyl ether and their derivatives. These alcohol solvents and glycol ethers can be used alone or in combination. By using water or water-containing alcohol solvents or glycol ethers, metal particles and inorganic polymers can be dispersed stably.
[0026] In the coating agent of the present invention, it is preferable to adjust the amount of solvent so that the solid content concentration is 0.1% by mass or more. If the solid content concentration is less than 0.1% by mass, a large amount of coating agent is required to form a coating film of a desired thickness, and the efficiency of the work tends to deteriorate. It is preferable to adjust the amount of solvent so that the solid content concentration is 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If the solid content concentration exceeds 30% by mass, the storage stability of the coating agent tends to decrease.
[0027] (catalyst) By adding a catalyst to the coating agent of the present invention, the hydrolysis reaction and / or polycondensation reaction of the inorganic polymer can be promoted. The type of catalyst is not particularly limited, but it is preferable to use, for example, a nonionic catalyst. When a nonionic catalyst is used, a superhydrophilic film can be formed even on a substrate that is highly corrosive to acids and bases, compared to when an acid catalyst or a base catalyst is used. Examples of nonionic catalysts include hydroxyaldehyde derivatives (or hydroxyketone derivatives), hydroxycarboxylic acid derivatives, allyl alcohol derivatives, and hydroxynitrile derivatives.
[0028] (Other additives) To the coating agent of the present invention, surfactants such as leveling agents for the purpose of smoothing the coating film, thickeners for the purpose of preventing cissing, and coloring pigments depending on the application can be added. Other additives can be added within a range that does not affect the hydrophilicity of the coating film formed by the coating agent of the present invention.
[0029] <First embodiment> The first embodiment of the present invention relates to a coating agent in which fine particles of a water-insoluble metal compound, an inorganic polymer, and transparent nanofibers are dispersed in a solvent. According to the embodiment of the present invention, it is possible to provide a coating agent that is excellent in hydrophilicity, warm water resistance, and coatability, and is capable of forming a coating film that is less susceptible to cracking.
[0030] (Transparent nanofiber) The coating agent of the present invention contains transparent nanofibers. Transparent nanofibers refer to, for example, fibers that are transparent and have a fiber diameter of 100 nm or less. Even when transparent nanofibers are used, the resulting coating film is excellent in transparency, hardness, and durability. Furthermore, by using transparent nanofibers, the adhesion to the substrate is not reduced even when the resulting coating film is made thick, and the hydrophilicity and durability (e.g., warm water resistance, heat resistance, temperature and humidity heat resistance, weather resistance, etc.) of the coating film are also improved. Furthermore, the coatability when applying the coating agent is improved, and a homogeneous coating film without color unevenness can be obtained.
[0031] It is believed that the coating film formed using the coating agent of the present invention exhibits greater superhydrophilicity and crack resistance because the transparent nanofibers are unevenly distributed on the substrate side of the coating film while the inorganic polymer is unevenly distributed on the surface of the coating film, resulting in greater unevenness (height difference between the unevenness) on the coating film surface.
[0032] The transparent nanofiber is preferably a nanofiber made of a polysaccharide having a six-membered ring structure. Examples of transparent nanofibers made of polysaccharides include cellulose nanofibers, or nanofibers having structural units of chitin or chitosan. The cellulose nanofiber is preferably a cellulose nanofiber containing structural units called microfibrils obtained by TEMPO treatment, or a cellulose nanofiber obtained by crushing biomass as a raw material.
[0033] The fiber diameter of the transparent nanofiber is preferably 2 nm or more. The fiber diameter of the transparent nanofiber is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 20 nm or less. If the fiber diameter of the transparent nanofiber is larger than 100 nm, the transparency tends to decrease.
[0034] The content of the transparent nanofiber in the coating agent is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the total solid content. If the content of the transparent nanofiber is less than 0.1% by mass, the effect of adding the transparent nanofiber may be insufficient. The content of the transparent nanofiber is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the total solid content. If the content of the transparent nanofiber is 10% by mass or more, the transparency, hardness, durability, and fluidity of the resulting coating film tend to decrease.
[0035] Second embodiment The second embodiment of the present invention is a coating agent in which water-insoluble metal compound particles and an inorganic polymer are dispersed in a solvent, and the metal compound particles have superhydrophilic functional groups. According to the coating agent of the second embodiment, the coating film produced using the coating agent not only has excellent superhydrophilicity, but also has excellent constant temperature and humidity resistance and heat resistance, and can exhibit excellent hydrophilicity for a long period of time.
[0036] In the second embodiment, the water-insoluble metal compound microparticles have a superhydrophilic functional group in the water-insoluble metal compound described above. When the metal compound has a superhydrophilic functional group, it is preferable that at least a part of the microparticle surface has the superhydrophilic functional group. It is sufficient that a part of the microparticles of the metal compound used has a superhydrophilic functional group on its surface, and it is not necessary that all the microparticles used have a functional group on their surface. In addition, the inorganic polymer may have a superhydrophilic functional group, and in this case, it can be formed by hybridizing the inorganic polymer with a compound having a superhydrophilic functional group. In the inorganic polymer, it is preferable that at least a part of the inorganic polymer surface has a superhydrophilic functional group, but it is not necessary that all the inorganic polymers used have a functional group on their surface.
[0037] The superhydrophilic functional group can be any functional group that imparts superhydrophilicity to the surfaces of the metal compound and inorganic polymer used in the present invention. In order to form a film that is excellent in superhydrophilicity, constant temperature and humidity resistance, and weather resistance, the superhydrophilic functional group is preferably a functional group represented by formula (1): [ka] (In formula (1), R 1 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms, A 1 is a monovalent cation.) A sulfonic acid group or a sulfonate group having a structure represented by formula (2): [ka] (In formula (2), R 2 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms, A 2 is a monovalent cation. Preferably, the functional group is a functional group containing a carboxylate group having a structure represented by the following formula:
[0038] In formula (1) and formula (2), R 1 and R 2 The number of carbon atoms is preferably 1 or more, and more preferably 2 or more, and more preferably 5 or less, and even more preferably 3 or less. When the number of carbon atoms is within such a range, the oxidation resistance of the film formed by using the coating agent of the present invention is excellent, and as a result, a film having excellent weather resistance can be formed.
[0039] Examples of methods for introducing sulfonic acid groups or sulfonate groups into fine particles of a water-insoluble metal compound include Formula (4): [ka] (In formula (4), R 1 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms, A 1is a monovalent cation.) can be obtained by hydrolysis reaction of the hydroxyl group of the compound represented by the formula (I) with the hydroxyl group present in the fine particles of the metal compound. The hydrolysis reaction can be carried out under acidic or alkaline conditions. In addition, when introducing sulfonic acid groups or sulfonate groups into the fine particles of the water-insoluble metal compound, for example, in the presence of the fine particles of the water-insoluble metal compound and a solvent, a reaction of synthesizing an inorganic polymer with a catalyst is carried out for 4 to 6 hours, and then a compound having a sulfonic acid group or a sulfonate group is added and further reacted for 2 to 3 hours. Alternatively, in the case where a refractive index adjuster is further included in the coating agent, for example, a reaction of synthesizing an inorganic polymer with a catalyst is carried out for 2 to 3 hours in the presence of the refractive index adjuster and a solvent, and then a fine particle of the water-insoluble metal compound is added and reacted for 2 to 3 hours, and then a compound having a sulfonic acid group or a sulfonate group is added and reacted for 2 to 3 hours.
[0040] Examples of the compound represented by formula (4) include ethanol-2-sulfonic acid, sodium ethanol-2-sulfonate, propanol-3-sulfonic acid, sodium propanol-3-sulfonate, butanol-4-sulfonic acid, sodium butanol-4-sulfonate, etc. Among these, it is preferable to use ethanol-2-sulfonic acid and sodium ethanol-2-sulfonate, since they can impart high hydrophilicity.
[0041] Examples of the polyether group to be introduced into the water-insoluble metal compound particles include polyalkylene oxide groups such as polyethylene oxide (PEO) groups and polypropylene oxide (PPO) groups. The molecular weight of the polyether group is not particularly limited as long as it exhibits superhydrophilicity, but it is preferable that the molecular weight is about 3000 or less.
[0042] A method for introducing polyether groups into fine particles of a water-insoluble metal compound can be achieved by hydrolysis of the hydroxyl groups of a polyalkylene oxide having hydroxyl groups at both ends with the hydroxyl groups present in the fine particles of the metal compound. The hydrolysis reaction can be carried out under acidic or alkaline conditions.
[0043] (Third embodiment) The third embodiment of the present invention is a coating agent in which fine particles of a water-insoluble metal compound, an inorganic polymer, and a refractive index control agent are dispersed in a solvent. According to the coating agent of the third embodiment, interference fringes caused by the refractive index difference between the obtained coating film and the substrate are suppressed.
[0044] The refractive index adjuster is preferably at least one metal oxide fine particle selected from the group consisting of Mg, Al, Ca, Ti, Zn, Nb, Zr, Sn, Ta, Ce, and Hf. Among these, when titanium oxide is used as the refractive index adjuster, the refractive index can be improved by adding a small amount to fine particles of a metal compound having a low refractive index such as silicon dioxide, since the refractive index of the compound is very high. In addition, when zirconia oxide is used as the refractive index adjuster, it does not cause a reaction that photodecomposes organic matter like titanium oxide, so there is an advantage that even if the coating agent is directly applied to a resin substrate for outdoor use, it is possible to impart superhydrophilicity without deteriorating the substrate.
[0045] As the refractive index adjuster, the difference between the refractive index of the water-insoluble metal compound fine particles and the refractive index of the refractive index adjuster is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more.If the difference between the refractive index of the water-insoluble metal compound fine particles and the refractive index adjuster is less than 0.1, the effect of adjusting the refractive index of the coating film tends to be insufficient.In addition, the greater the difference between the refractive index of the water-insoluble metal compound fine particles and the refractive index adjuster, the greater the effect of adding the refractive index adjuster.
[0046] The average particle size of the metal oxide fine particles is preferably 1 nm or more, more preferably 3 nm or more. The average particle size of the metal fine particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 35 nm or less. By using metal oxide fine particles having such a particle size as a refractive index adjuster, the transparency of the obtained coating film can be improved by suppressing interference fringes. In addition, a small particle size is preferable because it does not affect the transparency of the obtained coating film.
[0047] The content (solid content) of the refractive index adjuster in the coating agent is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on the total content (solid content) of the metal fine particles and the inorganic polymer. If the content of the refractive index adjuster is less than 5% by mass, the effect of suppressing interference fringes in the obtained coating film may not be sufficient. In addition, the content of the refractive index adjuster in the coating agent is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 65% by mass or less, and particularly preferably 60% by mass or less, based on the total content of the metal fine particles and the inorganic polymer. If the content of the refractive index adjuster exceeds 80% by mass, the transparency of the obtained coating film tends to decrease or the hydrophilicity tends to decrease.
[0048] (Method of manufacturing coating agent) The coating agent of the first embodiment of the present invention is obtained, for example, by adding transparent nanofibers to a mixed dispersion in which metal fine particles and inorganic polymers are dispersed in a solvent, and dispersing the mixture by stirring. Specifically, a dispersion of transparent nanofibers in water, alcohol, or glycol ether is added to the mixed dispersion of metal fine particles and inorganic polymers. The coating agent of the second embodiment of the present invention is obtained, for example, by adding metal fine particles having superhydrophilic groups introduced therein and a solvent to an inorganic polymer, and dispersing the mixture by stirring. The coating agent of the third embodiment of the present invention is obtained, for example, by adding transparent nanofibers to a mixed dispersion of metal fine particles and inorganic polymers, and dispersing the mixture by stirring. Specifically, a dispersion of transparent nanofibers in water, alcohol, or glycol ether is added to the mixed dispersion of metal fine particles and inorganic polymers.
[0049] (Method of forming coating film) Methods for forming a coating film on a substrate using the coating agents of the first to third embodiments of the present invention include a method for applying the coating agent to the surface of the substrate and a method for immersing the substrate in the coating agent. The method for applying the coating agent to the surface of the substrate is particularly preferred because it is simple, low cost, and allows easy control of the required thickness of the film.
[0050] The coating method is not particularly limited, and any known technique may be used, such as spin coating, dipping, spraying, flow coating, bar coating, roller coating, reverse coating, flexography, printing, or the like.
[0051] In order to improve the adhesion between the substrate and the coating film, the surface of the substrate may be pretreated by a method such as corona discharge treatment, glow discharge treatment, treatment with ionizing active rays such as ultraviolet rays, electron beams or radiation, surface roughening treatment, chemical treatment or primer treatment.
[0052] The substrate to be coated may be glass, plastic, metal, ceramics, or the like.
[0053] A coating film is formed by drying the coating agent applied to the surface of the substrate. The coating agent of the present invention can form a coating film without any problems even when dried at room temperature. When drying, it is preferable to heat at 60°C or higher, and more preferable to heat at 120°C or higher. It is preferable to heat at 600°C or lower, and more preferable to heat at 300°C or lower. The heating conditions are not particularly limited, but may be continuous or batch type, and may be heated at normal pressure or reduced pressure. When the coating agent is left to stand at room temperature for a certain period of time before the heat treatment, a more uniform coating film can be formed.
[0054] (Method of applying coating agent) The coating agents of the first to third embodiments of the present invention can be applied by the following method. By using the following coating agent application method, a coating film can be obtained in a short time of about one minute to several minutes.
[0055] If the substrate is solid wood and the surface to be coated is clean, (1) A method in which a coating agent is applied to a surface to be coated and then dried; (2) A method in which a coating agent is applied to the surface to be coated, and before the coating agent dries completely, the surface is washed with a cleaning liquid such as water or an organic solvent, and then dried. On the other hand, if the surface to be coated is dirty, (1) A method in which the surface to be coated is cleaned with alcohol or detergent, and then the coating agent is applied and dried before the surface is completely dry. (2) A method in which the surface to be coated is cleaned with alcohol or detergent, and before the surface is completely dry, the coating agent is applied, the surface is washed with a cleaning liquid such as water or an organic solvent, and then dried. (3) A method in which the surface to be coated is washed with alcohol or detergent, water stains and soapy dirt on the surface are polished off with an abrasive, the surface is washed off with a cleaning liquid such as water or an organic solvent, and before the surface to be coated is completely dry, a coating agent is applied and then dried. (4) A method in which the surface to be coated is washed with alcohol or detergent, water stains and soapy dirt on the surface are polished off with an abrasive, the surface is washed off with water or an organic solvent, and before the surface is completely dry, the coating agent is applied, the surface is washed off with water or an organic solvent, and then the surface is dried. Examples include:
[0056] The surface to be coated is not particularly limited, and examples thereof include silicate compounds such as glass, plastics, metals such as aluminum and stainless steel, and ceramics such as metal oxides. Among them, the surface to be coated is preferably glass, a mirror, or a ceramic. Water stains and soap stains on the surface to be coated can be washed and removed with alcohol, detergent, or the like. Water stains and soap stains on the surface to be coated can also be removed by polishing with a polishing agent. When the surface to be coated is glass or a mirror, it is preferable to use a polishing agent for glass as the polishing agent. By using a polishing agent for glass, the hydrophilicity of the obtained coating film tends to be improved, or the period during which the hydrophilicity is maintained tends to be longer. The time required to remove water stains and soap stains from the surface to be coated with alcohol, detergent, or a polishing agent can be, for example, 10 seconds to several tens of seconds.
[0057] Next, the detergent and polishing agent on the surface are washed away with a cleaning liquid such as water or an organic solvent. When water is used as the cleaning liquid, running water can be used. The time for washing away the detergent and polishing agent on the surface with running water can be, for example, several seconds to 10 and a half seconds.
[0058] Next, while the cleaning liquid adhering to the surface of the glass or mirror is not completely dried and still remains, any of the coating agents according to the first to third embodiments of the present invention is applied. The coating agent is preferably applied by a spray method. Application by the spray method can be carried out in, for example, several seconds to 10 and a few seconds.
[0059] The applied coating agent can be dried at room temperature (5 to 35°C). A part of the applied coating agent dries to form a coating film, but before the entire coating agent dries, the applied surface can be washed using a washing liquid. Water or an organic solvent can be used as the washing liquid. When water is used as the washing liquid, running water can be used. The time for washing the surface of the coating film with running water can be, for example, several seconds to 10 and a few seconds.
[0060] By drying the cleaning liquid, glass, mirror, or ceramics on which a coating film has been formed can be obtained. The cleaning liquid can be dried naturally at room temperature or by heating. In the case of natural drying, the cleaning liquid can be dried in a few minutes to a few hours. The obtained coating film can maintain its hydrophilicity for a period of about 2 weeks to 3 months.
[0061] (Coating film) The thickness of the coating film in the first to third embodiments of the present invention is preferably 5 nm or more, more preferably 100 nm or more, and even more preferably 500 nm or less. If the thickness of the coating film is less than 5 nm, the hydrophilicity tends to decrease. The thickness of the coating film is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 2 μm or less. If the thickness of the coating film is greater than 10 μm, the adhesion to the substrate tends to decrease, and the coating film tends to peel off easily.
[0062] The coating film formed by using the coating agent according to the first to third embodiments of the present invention is excellent in hydrophilicity and exhibits superhydrophilicity. Note that superhydrophilicity refers to a static contact angle of the coating film on the substrate surface with water of 10° C. or less. The contact angle is a value measured by the θ / 2 method.
[0063] (Application) The applications of the coating agents according to the first to third embodiments of the present invention are not particularly limited, and they can be used for surface coating of buildings, heat exchangers and heat pipes, etc. In addition, they can be used for surface coating of eyeglass lenses, camera lenses, underwater goggles, car windows, helmet shields, mirrors and lenses used in humid places, etc. EXAMPLES
[0064] The coating agent of the present invention will be described below using examples, but the present invention is not limited to the following examples.
[0065] (Example 1; Coating agent of the first embodiment) Under a nitrogen atmosphere, 20.9 g of tetraethoxysilane (manufactured by Tama Chemical Industries Co., Ltd.), 30.1 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-XS, Sears particle size 4 to 6 nm, solid content 20 wt%, solvent: water), 8.4 g of ethanol as a solvent, and 40.7 g of ion-exchanged water were added to a reaction vessel, and nitric acid (manufactured by Kanto Chemical Co., Ltd., product name: nitric acid 1.38) was added as a catalyst so that the pH of the entire solution was 2. The mixture was stirred at 40°C for 9 hours to obtain an inorganic polymer solution (A).
[0066] Next, 2% by mass of chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) as a transparent nanofiber and 0.7% by volume of ethanol as a solvent were added to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to obtain a coating agent. The solid content concentration of the obtained coating agent was 2% by mass.
[0067] The obtained coating agent was applied to the surface of a 76 mm x 52 mm glass substrate (manufactured by Matsunami Glass Industry Co., Ltd., thickness 1.5 mm) by the bar coating method using a bar coater (bar No. 7), and then heated and dried at 150°C for 15 minutes to obtain a coating film.
[0068] <Evaluation> The coating films obtained on the glass substrate and the polycarbonate substrate were subjected to tests for initial physical properties and durability evaluation. Specifically, the initial physical properties were evaluated as appearance, hydrophilicity, adhesion test by cross-cut test according to JIS K 5600-5-6:99, scratch hardness test by pencil method according to JIS K 5600-5-4:99, steel wool resistance, and alcohol resistance. In addition, the durability of the obtained coating film was evaluated by measuring the water contact angle after the test for warm water resistance, heat resistance, moist heat resistance, abrasion resistance, and weather resistance. The evaluation methods for each are as follows.
[0069] (Appearance; Transparency) The transmittance of the glass substrate on which the coating film was formed was measured using a haze meter (HM-150, manufactured by Murakami Color Laboratory Co., Ltd.) The coating film obtained in Example 1 was transparent.
[0070] (hydrophilicity; water contact angle) The static contact angle between the surface of the coating film and a water droplet was measured using a contact angle measuring device (FAMAS, manufactured by Kyowa Interface Science Co., Ltd.) by the θ / 2 method. The static contact angle of the coating film surface obtained in Example 1 was less than 10°.
[0071] (Adhesion) According to JIS K 5600-5-6:99, a cutter blade was placed perpendicular to the coating film, and six cuts were made in parallel at 1 mm intervals, and then six cuts were made perpendicular to the coating film by changing the direction by 90°. A tape was taken out to a length of 75 mm, and the tape was applied to the part of the coating film cut into a grid, and the tape was rubbed firmly with a finger so that the coating film could be seen through. The tape was attached and pulled off at an angle close to 60° in about 1 second. The amount of adhesion was evaluated according to the JIS classification of 0 to 5. The amount of adhesion when the coating film obtained in Example 1 was used was classified as 0.
[0072] (Scratch hardness) According to JIS K 5600-5-4:99, a straight line of 7 mm was drawn and the type of mark on the coating film surface was evaluated by visual inspection. The scratch hardness of the coating film surface obtained in Example 1 was evaluated to be 6H.
[0073] (Steel wool resistance) 500g / cm using #0000 steel wool 2 The central portion of the coating film surface was rubbed back and forth 10 times under the load condition, and the surface change was visually observed. No scratches were found on the surface of the coating film obtained in Example 1.
[0074] (Alcohol resistance) The surface of the coating film was wiped 100 times with absorbent cotton (15 mm x 15 mm, 1 ml of impregnated cotton) soaked in pure ethanol, and the surface change was visually observed. The surface of the coating film obtained in Example 1 did not change before and after the test.
[0075] (Hot water resistance) The surface of the coating film on the glass substrate was kept in contact with 50°C hot water at 100 ml / hour for 100 hours, and the change in the appearance of the coating film was visually confirmed, and the static contact angle of the coating film surface with water was measured. There was no visual change, and the static contact angle was less than 10° even after the test.
[0076] (Heat resistance) The glass substrate on which the coating film was formed was left to stand at 150° C. for 100 hours, and the change in the appearance of the coating film was visually confirmed, and the static contact angle of the coating film surface with water was measured.
[0077] (Moisture and heat resistance) The glass substrate on which the coating film was formed was left to stand for 100 hours under conditions of 65° C. and 95% RH, and the change in the appearance of the coating film was visually confirmed, and the static contact angle of the coating film surface with water was measured.
[0078] (Wear resistance) The glass substrate on which the coating film was formed was attached to a flat reciprocating test stand and rubbed with a 20 x 20 mm flat frictional device (Crecia EF, manufactured by Nippon Paper Crecia Co., Ltd.) under a load of 500 g, after which the static contact angle of the coating film surface with water was measured. The static contact angle was less than 10°.
[0079] (weather resistance) A xenon arc lamp weather resistance test was conducted in accordance with JIS B 7754:91. A xenon lamp with a continuous spectrum of 300 to 400 nm was used, with a black panel temperature of 63°C and 60 W / m 2 The coating film surface was irradiated for 1000 hours by repeating a cycle of 102 minutes of irradiation, followed by 18 minutes of irradiation and water spraying for 120 minutes with a lamp intensity of 10 ...
[0080] (Example 2: Coating agent of the first embodiment) A coating agent was produced in the same manner as in Example 1, except that the inorganic polymer solution (A) of Example 1 was used and cellulose nanofiber (manufactured by Sugino Machine Ltd., product name: BiNFi-s AMa-10002) was used as the transparent nanofiber in the production of the coating agent of Example 1, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0081] (Example 3; Coating agent of the first embodiment) In the preparation of the inorganic polymer solution (A) in Example 1, except that the amount of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-S, BET particle size 8-11 nm, solid content 30 wt%, solvent: water) was changed to 20.0 g and the amount of ion-exchanged water was changed to 51.2 g, the same procedure as in Example 1 was followed to prepare a coating agent, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0082] (Example 4; Coating agent of the first embodiment) In the preparation of the inorganic polymer solution (A) in Example 1, except that the amount of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-30, BET particle size 10-15 nm, solid content 30 wt%, solvent: water) was changed to 20.0 g and the amount of ion-exchanged water was changed to 51.2 g, the same procedure as in Example 1 was followed to prepare a coating agent, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0083] (Example 5; Coating agent of the first embodiment) A coating agent was produced in the same manner as in Example 1, except that in the production of the inorganic polymer solution (A) in Example 1, colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size according to dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water) was used at 30.1 g, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0084] (Example 6; Coating agent of the first embodiment) In the preparation of the inorganic polymer solution (A) of Example 1, the amount of tetraethoxysilane was changed to 16.7 g, the amount of spherical colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8-11 nm, solid content 20 wt%, solvent: water) was changed to 36.1 g, the amount of ethanol was changed to 6.7 g, and the amount of ion-exchanged water was changed to 41.0 g. The coating agent was prepared in the same manner as in Example 1, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0085] (Example 7; Coating agent of the first embodiment) A coating agent was produced in the same manner as in Example 6, except that the inorganic polymer solution (A) of Example 6 was used and cellulose nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s AMa-10002) was used as the transparent nanofiber in the production of the coating agent of Example 6, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0086] (Example 8; Coating agent of the first embodiment) In the preparation of the inorganic polymer solution (A) of Example 1, the amount of tetraethoxysilane was changed to 20.8 g, the amount of chain colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size measured by dynamic light scattering method: 40 to 100 nm, solid content: 15 wt%, solvent: water) was changed to 40.0 g, the amount of ethanol was changed to 8.3 g, and the amount of ion-exchanged water was changed to 30.8 g. A coating agent was prepared in the same manner as in Example 1, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0087] (Example 9; Coating agent of the second embodiment) Under a nitrogen atmosphere, 18.8 g of tetraethoxysilane (manufactured by Tama Chemical Industries Co., Ltd.), 30.1 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-XS, Sears particle size 4 to 6 nm, solid content 20 wt%, solvent: water), 7.5 g of ethanol as a solvent, 37.6 g of ion-exchanged water, and nitric acid (manufactured by Kanto Chemical Co., Ltd., product name: nitric acid 1.38) as a catalyst were placed in a reaction vessel so that the pH of the entire solution was 2, and stirred at 40 ° C. for 6 hours. Then, 6.0 g of a sulfonate compound (manufactured by Kiyosumi Laboratory Co., Ltd., product name: KS-S10X) was added as a compound that imparts a superhydrophilic functional group, and the mixture was further stirred at 40 ° C. for 3 hours to obtain an inorganic polymer solution (A). Next, ethanol was added as a solvent at a volume ratio of 0.7% relative to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to obtain a coating agent, which was then evaluated for its initial physical properties and durability. The results are shown in Table 1.
[0088] (Example 10; Coating agent of the second embodiment) A coating agent was produced in the same manner as in Example 9, except that the inorganic polymer solution (A) of Example 9 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 9, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0089] (Example 11; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 9, 7.5 g of methanol was used instead of ethanol as a solvent, and the mixture was stirred at 40° C. for 4 hours, followed by adding a sulfonate compound and stirring at 40° C. for 2 hours. The inorganic polymer solution (A) was prepared in the same manner as in Example 9. 0.7% by volume of methanol was added as a solvent to the total amount of the inorganic polymer solution (A), and the mixture was stirred at 25° C. for 1 hour to prepare a coating agent, which was evaluated for its initial physical properties and durability. The results are shown in Table 1.
[0090] (Example 12; Coating agent of the second embodiment) A coating agent was produced in the same manner as in Example 11, except that the inorganic polymer solution (A) of Example 11 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 11, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0091] (Example 13; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 11, except that the colloidal silica was changed to 30.1 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 9, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0092] (Example 14; Coating agent of the second embodiment) A coating agent was produced in the same manner as in Example 13, except that the inorganic polymer solution (A) of Example 13 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 13, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0093] (Example 15; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 9, tetraethoxysilane was changed to 20.7 g, colloidal silica to 18.7 g, and methanol as a solvent was changed to 15.5 g and ion-exchanged water to 28.0 g. After stirring at 40°C for 4 hours, 8.9 g of a sulfonate compound (manufactured by Kiyosumi Laboratory, product name: KS-S10X) was added, and the mixture was stirred at 40°C for 2 hours. The inorganic polymer solution (A) was prepared in the same manner as in Example 9. Methanol was added as a solvent at a volume ratio of 0.7% relative to the total amount of this inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to prepare a coating agent, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0094] (Example 16; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 15, the inorganic polymer solution (A) was obtained in the same manner as in Example 15, except that the amount of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water) was changed to 8.4 g. A coating agent was prepared in the same manner as in Example 15, except that chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) was added as a transparent nanofiber to the inorganic polymer solution (A) in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A), and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0095] (Example 17; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 9, the amount of tetraethoxysilane was changed to 15.0 g, the amount of colloidal silica was changed to 36.0 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8-11 nm, solid content 20 wt%, solvent: water), the amount of ethanol was changed to 19.5 g, the amount of ion-exchanged water was changed to 24.8 g, and the amount of sulfonic acid compound was changed to 4.8 g. A coating agent was prepared in the same manner as in Example 9, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0096] (Example 18; Coating agent of the second embodiment) A coating agent was produced in the same manner as in Example 17, except that the inorganic polymer solution (A) of Example 17 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 17, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0097] (Example 19; Coating agent of the second embodiment) In the preparation of the inorganic polymer solution (A) of Example 9, the colloidal silica was changed to 40.1 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size measured by dynamic light scattering method: 40 to 100 nm, solid content: 15 wt%, solvent: water), 9.9 g of ethanol, and 25.5 g of ion-exchanged water. A coating agent was prepared in the same manner as in Example 9, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0098] (Example 20; Coating agent of the second embodiment) A coating agent was produced in the same manner as in Example 19, except that the inorganic polymer solution (A) of Example 19 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 19, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0099] (Example 21; Coating agent of the third embodiment) In a nitrogen atmosphere, 20.6 g of tetraethoxysilane (manufactured by Tama Chemical Industries Co., Ltd.), 15.0 g of ethanol as a solvent, 17.5 g of ion-exchanged water, and 18.7 g of titania sol (manufactured by Taki Chemical Industries Co., Ltd., product name: Tinoc AM-15, secondary particle diameter 20 nm, solid content 15 wt%) as a refractive index adjuster were placed in a reaction vessel, and stirred at 40° C. for 3 hours. After that, colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) S 24.5 g of T-XS, Sears particle size 4-6 nm, solid content 20 wt%, solvent: water) was added and stirred at 40°C for 3 hours, after which 3.8 g of a sulfonate compound (Kiyosumi Laboratory, product name: KS-S10X) was added as a compound that imparts superhydrophilic functional groups, and nitric acid (Kanto Chemical, product name: nitric acid 1.38) was added as a catalyst to the reaction vessel so that the pH of the entire solution was 2, and the mixture was stirred at 40°C for 3 hours to obtain an inorganic polymer solution (A). Next, ethanol was added as a solvent at a volume ratio of 0.7% relative to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to produce a coating agent. The initial physical properties and durability were evaluated in the same manner as in Example 1, except that a film was formed using a bar coater (bar No. 12). The results are shown in Table 1.
[0100] (Example 22; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 21, except that the inorganic polymer solution (A) of Example 21 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 21, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0101] (Example 23; Coating agent of the third embodiment) In the preparation of inorganic polymer solution (A) of Example 21, tetraethoxysilane is changed to 14.6g, ethanol to 19.8g, ion-exchanged water to 12.4g, titania sol is changed to titania sol (manufactured by Taki Chemical Industry Co., Ltd., product name: Tinoc M-6, secondary particle diameter 10nm, solid content 6wt%) 33.2g, colloidal silica to 17.4g, sulfonate compound to 2.7g, except that, a coating agent is prepared in the same manner as in Example 21, and initial physical properties and durability are evaluated. The results are shown in Table 1.
[0102] (Example 24; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 23, except that the inorganic polymer solution (A) of Example 23 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 23, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0103] (Example 25; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 21, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 21, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0104] (Example 26; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 25, except that the inorganic polymer solution (A) of Example 25 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 25, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0105] (Example 27; Coating agent of the third embodiment) In the production of the inorganic polymer solution (A) of Example 21, tetraethoxysilane was changed to 14.6g, ethanol to 19.8g, ion-exchanged water to 12.4g, titania sol was changed to titania sol (manufactured by Taki Chemical Co., Ltd., product name: Tinoc M-6, secondary particle diameter 10nm, solid content 6wt%) to 33.2g, colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle diameter of dynamic light scattering method 40-100nm, solid content 20wt%, solvent: water) to 17.4g, and sulfonate compound was changed to 2.7g. A coating agent was produced in the same manner as in Example 21, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0106] (Example 28; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 27, except that the inorganic polymer solution (A) of Example 27 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 27, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0107] (Example 29; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 21, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8 to 11 nm, solid content 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 21, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0108] (Example 30; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 29, except that the inorganic polymer solution (A) of Example 29 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 29, and the initial physical properties and durability were evaluated. The results are shown in Table 1.
[0109] (Example 31; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 21, the ion-exchanged water was changed to 9.3 g, and the colloidal silica was changed to 32.7 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 15 wt%, solvent: water), but the same procedure was followed to prepare a coating agent, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0110] (Example 32; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 31, except that the inorganic polymer solution (A) of Example 31 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 31, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0111] (Example 33; Coating agent of the third embodiment) In a nitrogen atmosphere, 19.2 g of tetraethoxysilane (manufactured by Tama Chemical Industry Co., Ltd.), 13.2 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-XS, Sears particle size 4 to 6 nm, solid content 20 wt%, solvent: water), 17.7 g of ethanol as a solvent, 9.2 g of ion-exchanged water, and 39.0 g of titania sol (manufactured by Taki Chemical Industry Co., Ltd., product name: Tinock AM-15, secondary particle size 20 nm, solid content 15 wt%) as a refractive index adjuster were placed in a reaction vessel, and stirred at 40 ° C. for 6 hours. 6.1 g of a sulfonate compound (manufactured by Kiyosumi Laboratory Co., Ltd., product name: KS-S10X) was added as a compound that imparts a superhydrophilic functional group, and nitric acid (manufactured by Kanto Chemical Co., Ltd., product name: nitric acid 1.38) was added as a catalyst to the reaction vessel so that the pH of the entire solution was 2, and the mixture was stirred at 40 ° C. for 3 hours to obtain an inorganic polymer solution (A). Next, ethanol was added as a solvent at a volume ratio of 0.7% relative to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to produce a coating agent, which was evaluated for initial physical properties and durability under the same conditions as in Example 1. The results are shown in Table 2.
[0112] (Example 34; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 33, except that the inorganic polymer solution (A) of Example 33 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 33, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0113] (Example 35; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 33, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 33, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0114] (Example 36; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 35, except that the inorganic polymer solution (A) of Example 35 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 35, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0115] (Example 37; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 33, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8 to 11 nm, solid content 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 33, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0116] (Example 38; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 37, except that the inorganic polymer solution (A) of Example 37 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 37, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0117] (Example 39; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 33, tetraethoxysilane was changed to 18.4 g, colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size by dynamic light scattering method 40 to 100 nm, solid content 15 wt%, solvent: water) 16.8 g, titania sol to 37.4 g, sulfonate compound to 4.7 g, and ethanol as a solvent was changed to 17.1 g and ion-exchanged water to 4.7 g. The coating agent was prepared in the same manner as in Example 33, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0118] (Example 40; Coating agent of the third embodiment) A coating agent was produced in the same manner as in Example 39, except that the inorganic polymer solution (A) of Example 39 was used and chitin nanofibers (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) were added as transparent nanofibers in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A) in the production of the coating agent of Example 39, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0119] (Example 41; Coating agent of the third embodiment) Under a nitrogen atmosphere, 22.7 g of tetraethoxysilane (manufactured by Tama Chemical Industry Co., Ltd.), 14.3 g of methanol as a solvent, 20.2 g of ion-exchanged water, and zirconia sol (manufactured by Sakai Chemical Industry Co., Ltd., product name: SZR-W, D 50 A reaction vessel was charged with 16.1 g of nitric acid (manufactured by Kanto Chemical Co., Ltd., product name: nitric acid 1.38) as a catalyst so that the pH of the entire solution was 2 throughout, and the mixture was stirred at 40°C for 2 hours. After that, 20.2 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-XS, Sears particle size 4 to 6 nm, solid content 20 wt%, solvent: water) was added and stirred for 2 hours. After that, 77.2 g of a sulfonate compound (manufactured by Kiyosumi Laboratory, product name: KS-S10X) was added as a compound that imparts superhydrophilic functional groups, and the mixture was stirred at 40°C for 2 hours to obtain an inorganic polymer solution (A). Next, 0.7% by volume of methanol was added as a solvent to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to produce a coating agent, which was then formed into a film using a bar coater (bar No. 12). The initial physical properties and durability were evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0120] (Example 42; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 41, ethanol was used instead of methanol as a solvent, and the mixture was stirred at 40°C for 3 hours, followed by adding colloidal silica, stirring at 40°C for 3 hours, and then adding a sulfonate compound and stirring at 40°C for 3 hours to prepare an inorganic polymer solution (A). Except for adding 2% by mass of chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) as a transparent nanofiber and 0.7% by volume of ethanol as a solvent, a coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0121] (Example 43; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 41, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0122] (Example 44; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 42, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 42, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0123] (Example 45; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 41, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8 to 11 nm, solid content 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0124] (Example 46; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 42, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8 to 11 nm, solid content 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 42, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0125] (Example 47; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 41, the amount of tetraethoxysilane was changed to 22.6 g, the amount of methanol as a solvent was changed to 14.0 g and the amount of ion-exchanged water was changed to 13.6 g, and the amount of colloidal silica was changed to 26.8 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size according to dynamic light scattering method: 40 to 100 nm, solid content: 15 wt%, solvent: water). Except for this, a coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0126] (Example 48; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 47, ethanol was used instead of methanol as a solvent, and the mixture was stirred at 40°C for 3 hours, followed by adding colloidal silica, stirring at 40°C for 3 hours, and then adding a sulfonate compound and stirring at 40°C for 3 hours to prepare an inorganic polymer solution (A). Except for adding 2% by mass of chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) as a transparent nanofiber and 0.7% by volume of ethanol as a solvent, a coating agent was prepared in the same manner as in Example 47, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0127] (Example 49; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 41, tetraethoxysilane was changed to 19.0 g, zirconia sol to 26.7 g, the solvent was changed to ethanol 16.5 g and ion-exchanged water 22 g, and the mixture was stirred at 40 ° C for 3 hours, after which colloidal silica was changed to 9.6 g, colloidal silica was added, and the mixture was stirred at 40 ° C for 3 hours, after which a sulfonate compound was added, and the mixture was stirred at 40 ° C for 3 hours to prepare an inorganic polymer solution (A). Except for adding 2 mass% chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name; BiNFi-s SFo-20002) as a transparent nanofiber and 0.7% by volume of ethanol as a solvent to the total amount of this inorganic polymer solution (A), a coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated under the same conditions as in Example 1. The results are shown in Table 2.
[0128] (Example 50; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 49, the colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-UP, average particle size measured by dynamic light scattering method: 40 to 100 nm, solid content: 20 wt%, solvent: water), and no transparent nanofibers were used in the preparation of the coating agent. Except for this, a coating agent was prepared in the same manner as in Example 49, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0129] (Example 51; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 49, except that colloidal silica was changed to colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OS, BET particle size 8 to 11 nm, solid content 20 wt%, solvent: water), a coating agent was prepared in the same manner as in Example 49, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0130] (Example 52; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) of Example 49, the colloidal silica was changed to 12.8 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size measured by dynamic light scattering method: 40 to 100 nm, solid content: 15 wt%, solvent: water), and 18.8 g of ion-exchanged water was used, and no transparent nanofibers were used in the preparation of the coating agent. A coating agent was prepared in the same manner as in Example 49, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0131] (Example 53; Coating agent of the third embodiment) Under a nitrogen atmosphere, 14.6 g of tetramethoxysilane (manufactured by Tama Chemical Industry Co., Ltd.), 21.9 g of methanol as a solvent, 12.1 g of ion-exchanged water, and zirconia sol (manufactured by Sakai Chemical Industry Co., Ltd., product name: SZR-W, D 50 45.3 g of a polymer solution (3.3 nm, solid content 30 wt%, solvent: water) and 6.4 g of a sulfonate compound (manufactured by Kiyosumi Laboratory, product name: KS-S10X) as a compound to impart superhydrophilic functional groups were added to a reaction vessel, and nitric acid (manufactured by Kanto Chemical Co., Ltd., product name: nitric acid 1.38) was added as a catalyst so that the pH of the entire solution was 2. The mixture was stirred at 40°C for 6 hours to obtain an inorganic polymer solution (A). Next, 2% by mass of chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) as a transparent nanofiber and 0.7% by volume of methanol as a solvent were added to the total amount of the obtained inorganic polymer solution (A), and the mixture was stirred at 25°C for 1 hour to produce a coating agent, which was then evaluated for its initial physical properties and durability. The results are shown in Table 2.
[0132] (Example 54; Coating agent of the third embodiment) In the preparation of the inorganic polymer solution (A) in Example 31, tetraethoxysilane was used in an amount of 15.8 g, ethanol in an amount of 20.7 g, ion-exchanged water in an amount of 17.7 g, and ceria sol (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., product name: CESL-30N, particle size D 50 A coating agent was produced in the same manner as in Example 31, except that the amount of the sintered material was changed to 13.9 g of 1000 nm (5-15 nm), the colloidal silica was changed to 25.1 g of colloidal silica (manufactured by Nissan Chemical Industries, Ltd., product name: Snowtex (registered trademark) ST-OUP, average particle size by dynamic light scattering method: 40-100 nm, solid content: 15 wt%, solvent: water), and the amount of the sulfonate compound was changed to 6.8 g, and the initial physical properties and durability were evaluated. The results are shown in Table 2.
[0133] Comparative Example 1 A coating agent was produced in the same manner as in Example 1, except that no transparent nanofibers were used in the production of the coating agent in Example 1, and the initial physical properties and durability were evaluated. The results are shown in Table 3.
[0134] Comparative Example 2 In the preparation of the inorganic polymer solution (A) in Example 21, the amount of ethanol was changed to 18.8 g, and no sulfonate compound was used, so that a coating agent was prepared in the same manner as in Example 21, and the initial physical properties and durability were evaluated. The results are shown in Table 3.
[0135] Comparative Example 3 In the preparation of the inorganic polymer solution (A) of Example 41, the amount of methanol was changed to 21.5 g, chitin nanofiber (manufactured by Sugino Machine Co., Ltd., product name: BiNFi-s SFo-20002) was added as a transparent nanofiber in an amount of 2 mass% relative to the total amount of the inorganic polymer solution (A), and no sulfonate compound was used. A coating agent was prepared in the same manner as in Example 41, and the initial physical properties and durability were evaluated. The results are shown in Table 3.
[0136] Comparative Example 4 In the preparation of the inorganic polymer solution (A) of Example 53, the amount of methanol was changed to 28.3 g, and no sulfonate compound was used, but the same procedure as in Example 53 was followed to prepare a coating agent, and the initial physical properties and durability were evaluated. The results are shown in Table 3.
[0137] (Evaluation; PCB change) The coating agent obtained in Example 1 was applied to the surface of a polycarbonate substrate (manufactured by Takiron CI Co., Ltd., thickness 1.5 mm) whose surface had been subjected to corona treatment by a bar coating method using a bar coater (bar No. 7), and the substrate was dried by heating at 120°C for 15 minutes to obtain a coating film. The corona treatment was performed using Corona Fit CFG-500 manufactured by Shinko Electric Co., Ltd. until the surface became hydrophilic. The coating agents obtained in Examples 33 to 40, 49 to 52, and Comparative Examples 1 to 3 were evaluated for their coating films under the same conditions as above, except that a polycarbonate substrate and bar coater bar No. 12 were used. The results are shown in Table 3.
[0138] The coating agents obtained in Example 53 and Comparative Example 4 were evaluated by applying the coating agent to the surface of an aluminum substrate (A6061P plate, 70 mm x 30 mm, thickness 0.3 mm) using a bar coater with bar No. 12, and then drying the coating by heating at 150°C for 15 minutes. The results are shown in Table 3.
[0139] [Table 1]
[0140] [Table 2]
[0141] [Table 3]
[0142] (Example 55) The coating agents obtained in Examples 1, 9, and 21 were each applied to a commercially available mirror having a glass surface by the following method. First, the surface of the mirror was washed with ethanol. Next, the coating agent was sprayed onto the surface of the mirror. The amount of coating was such that the thickness of the coating film after drying was 500 nm or less. Immediately after application, before all of the coating agent had dried, the applied surface was washed with running water. It took about 1 minute to wash the mirror surface with ethanol and to rinse the applied surface of the coating agent with running water. Then, the water attached to the surface of the obtained coating film was dried at 20°C for 1 hour.
[0143] The obtained coating films all had a water contact angle of 10° or less, the surface of the coating film did not become cloudy due to breath, and a water film was formed on the surface even when water was sprayed on it by spraying. Furthermore, the obtained coating films all had a water film formed on the surface even when sprayed with water after being left in a bathroom for 2 months from the formation of the coating film. Furthermore, the obtained coating films all had a water film formed on the surface even when sprayed with water after being left outdoors for 3 months from the formation of the coating film. On the other hand, the commercially available glass mirror used in this example itself had a water contact angle of 45°, the surface of the mirror became cloudy due to breath, and a water film was not formed on the surface even when water was sprayed on it by spraying.
[0144] (Example 56) The coating agents obtained in Examples 1, 9, and 21 were each coated on an aluminum plate by the following method. First, the surface was washed with ethanol. Next, the coating agent was spray-coated on the surface. The coating amount was such that the thickness of the coating film after drying was 500 nm or less. Immediately after coating, before all of the coating agent had dried, the coated surface was washed with running water. It took about 1 minute to wash the surface with ethanol and to rinse the coated surface with running water. Then, the water attached to the surface of the obtained coating film was dried at 20°C for 1 hour. For all of the obtained coating films, a water film was formed on the surface even when water was sprayed by a spray.
[0145] (Example 57) The coating agents obtained in Examples 1, 9, and 21 were each coated on a stainless steel plate by the following method. First, the surface was washed with ethanol. Next, the coating agent was sprayed onto the surface. The coating amount was such that the thickness of the coating film after drying was 500 nm or less. Immediately after application, before all of the coating agent had dried, the coated surface was washed with running water. It took about 1 minute to wash the surface with ethanol and to rinse the coated surface with running water. Then, the water attached to the surface of the obtained coating film was dried at 20°C for 1 hour. For all of the obtained coating films, a water film was formed on the surface even when water was sprayed by a spray.
Claims
1. A coating agent in which fine particles of a water-insoluble metal compound and an inorganic polymer are dispersed in a solvent.
2. 2. The coating agent of claim 1, wherein the metal compound is silicon dioxide.
3. 3. The coating agent according to claim 1, wherein the inorganic polymer has a structure obtained by condensing a silicon alkoxide.
4. The coating agent according to any one of claims 1 to 3, wherein the coating agent has a solid content concentration of 0.1 to 30 mass%.
5. 5. The coating agent according to claim 1, wherein the mass ratio of the metal fine particles to the inorganic polymer is 20 / 80 to 90 / 10.
6. 6. The coating agent according to claim 1, wherein the metal particles have a particle size of 1 to 100 nm.
7. The coating agent according to any one of claims 1 to 6, wherein the fine particles of the metal compound have a superhydrophilic functional group.
8. The superhydrophilic functional group has the formula (1): 【Chemistry 1】 (In the formula (1), R 1 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms; A 1 is a monovalent cation.) a sulfonic acid group or a sulfonate group having a structure represented by formula (2): 【Chemistry 2】 (In the formula (2), R 2 is a structural unit derived from an alkyl group having 1 to 10 carbon atoms; A 2 is a monovalent cation. The coating agent according to claim 7, wherein the functional group is a carboxylate group, a polyether group, or a ureido group represented by the formula (I):
9. The coating agent according to any one of claims 1 to 6, further comprising a refractive index control agent dispersed in the solvent.
10. 10. The coating agent according to claim 9, wherein the refractive index adjusting agent is fine particles of an oxide of at least one metal selected from the group consisting of Mg, Al, Ca, Ti, Zn, Nb, Zr, Sn, Ta, Ce, and Hf.
11. An article having a coating film formed by applying the coating agent according to any one of claims 1 to 10.
12. A coating method for coating a coating agent in which fine particles of a water-insoluble metal compound and an inorganic polymer are dispersed in a solvent, comprising the steps of: A first cleaning step of cleaning the surface to be coated with a cleaning liquid; a coating step of coating the coating agent on a surface to be coated while the cleaning liquid remains on the surface; The coating method according to claim 1,
13. A second cleaning process is performed to clean the coated surface using a cleaning solution before all of the coating agent has dried. The coating method according to claim 12, comprising:
14. 14. The coating method according to claim 12 or 13, wherein the surface to be coated is a metal oxide or a silicate compound.
15. The coating surface is glass, The coating method according to claim 14, wherein the first cleaning step is performed using an abrasive for glass.
16. 15. The coating method according to claim 14, wherein the surface to be coated is made of ceramics.
Citation Information
Patent Citations
Production method for photocatalytic coating film and photocatalytic material
JP2002320917A
Composition for use in antistatic film formation
JP2007106936A
Silicone coating composition, method for producing the same, and coated article
JP2008094956A
Coating for forming transparent antistatic film, transparent antistatic film and method for producing the same
JP2008201879A
Antifogging film article
JP2011213555A